2014
DOI: 10.3233/jad-132252
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hippocampal Blood Flow in Sedentary Older Adults at Genetic Risk for Alzheimer's Disease

Abstract: Resting cerebral blood flow (CBF) decreases with age; however regulatory increases in hippocampal CBF have been associated with genetic risk (Apolipoprotein E [APOE] ε4 carriers) for Alzheimer’s disease (AD). Although physical activity (PA) exerts beneficial effects on CBF in healthy elders, the effects of sedentary behaviors on CBF remain unknown. We measured resting hippocampal CBF (via arterial spin labeling magnetic resonance imaging) and sedentary time/PA (via accelerometry) on 33 cognitively healthy adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 66 publications
1
36
1
Order By: Relevance
“…An increase in regional CBF in the preclinical phase of AD when cognitive performance is preserved (as shown in Table ) has been suggested as a compensatory response to the accumulation of Aβ pathology . Other studies also found significant increased perfusion in nondemented elderly subjects at risk for AD, which was also interpreted as a compensatory mechanism leading to a need for extra glucose and oxygen to support neuronal activity . Several functional MRI (fMRI) studies of CN Aβ + also reported increased neural activity during cognitive activity in comparison with young people or CN Aβ– older participants .…”
Section: Discussionsupporting
confidence: 84%
“…An increase in regional CBF in the preclinical phase of AD when cognitive performance is preserved (as shown in Table ) has been suggested as a compensatory response to the accumulation of Aβ pathology . Other studies also found significant increased perfusion in nondemented elderly subjects at risk for AD, which was also interpreted as a compensatory mechanism leading to a need for extra glucose and oxygen to support neuronal activity . Several functional MRI (fMRI) studies of CN Aβ + also reported increased neural activity during cognitive activity in comparison with young people or CN Aβ– older participants .…”
Section: Discussionsupporting
confidence: 84%
“…We expect findings will further elucidate the role of vascular dysregulation in AD and support further development of vasoprotective treatments. Given recent findings associating regulatory elevations of CBF in the MTL with sedentary behavior in APOE ε4 carriers [62], and increased CBF in the anterior cingulate following an exercise intervention in older adults [63], future research must exploit the potential disease-modifying role that pharmacological [4] and behavioral lifestyle factors, such as exercise, diet, and cognitive engagement may play in the regulation of CBF and prevention of AD.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported a relationship between sedentary time and CBF that was modified by genetic risk in the left hippocampus, such that APOE ε4 carriers showed higher CBF as a function of longer sedentary time relative to non-carriers. We believe this suggests that sedentary time may act as a behavioral risk factor possibly exacerbating the regulatory increases in CBF usually seen in APOE ε4 carriers (Zlatar et al 2014). Preliminary work currently being collected by our research group suggests that there is a strong positive association between higher sedentary time (measured objectively via accelerometry) and higher levels of CSF tau.…”
Section: Can Behavioral Interventions Modify Cbf To Improve Cognitmentioning
confidence: 92%